การศึกษาศักยภาพทางการตลาดของห้องชุดสองชั้น - จักรพงษ์ มัณฑุกานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This study aimed to study the market potential of double floor condominium units in the real estate market including the general characteristics of the residents in the double floor condominium units no larger than 200 square meters, double floor condominium units in low-rise buildings of two projects in Nonthaburi and high-rise buildings of two projects in the economic area in Bangkok. The tools used in this research consist of interviews with the developers of the real estate market which run the project, including interviews and a questionnaire for the people who live in the units. The results of the interviews with the developers showed the initiative to do a project with a double floor condominium unit have been influenced by the real estate system of foreign-developed units. There is also a reason for the marketing of property to differentiate from competitors in the market for today. The research found that the developers had to separate the locations and focus on the economic area or close to the economic area of Bangkok. Another focus area are those similar to the economic area in Bangkok which could serve residents who need to live in the economic area of Bangkok or nearby and are interested in double floor condominium units. They desire a lifestyle that makes them different from others and they want more privacy area in their own unit as well. They are also need the more living space in condominium units that can match to their lifestyle more and they want a different style like a vertical space for the units. The research found that most of the target market was living in a two-floor single-family home or in a home with extended family, which influenced their decision to move into a two storied space. This is the main reason that real estate developers began to develop a two-floor condominium units. Developer realized the potential for double floor condominium units in the future. The results showed that residents in the two-floor condominium units consist of homeowners more than renters. The two-floor condominium units are developed in newer suburban areas more than inner Bangkok, because there is a high potential for these areas to be future economic areas of Bangkok. Also, the value of the land is affordable, there is access to the transit system and also some jobs. The target group of residents can easily buy these places. The supply and demand factors have been corresponding to the economy more than in the heart of Bangkok. There is a lot of demand in the new urban areas and good prospects for investment benefits in the future.